[DTPA-(PABn)-Leu5]-des-acyl ghrelin(1–5) as a new carrier of radionuclides and potential precursor of radiopharmaceuticals. Issue 2 (February 2018) - Wójciuk, Grzegorz; Kruszewski, Marcin
Abstract : Background: Ghrelin is a peptide consisting of 28 aminoacids and an octadecyl side chain (acyl group) binding to the growth hormone secretagogue receptor type 1a (GHS-R1a). Its des-acylated form, des-acyl ghrelin (DAG) binds to the corticotropin releasing factor receptor type 2a (CRF2a) located on endocrine cancer cells such as the prostate carcinoma cell line DU 145. Aim: The aim of this study is to develop a new DAG-based carrier of radionuclides with potential application in therapy. Materials and methods: Trunctated C-terminal five aminoacids chain of the DAG peptide (H2N-Gly-Ser-Ser-Phe-Leu-COOH) was linked to DTPA to obtain [DTPA-(PABn)-Leu5]-DAG(1–5). For therapeutic application the lutetium-177 (177Lu) radionuclide was coordinated to the peptide. To determine biological and chemical properties of newly synthesized radiopharmaceutical, two iodine-131 (131I)-labelled compounds were used: [131I]-Tyr4-DAG(1–5) and full length [131I]-DAG(1–28) together with their nonradioactive forms: DAG(1–28) and DAG(1–5). Results: Identical HPLC elution profiles of [177Lu-DTPA-(PABn)-Leu5]-DAG(1–5) before and after incubation with human serum proved its stability. The lipophilicity profile of [177Lu-DTPA-(PABn)-Leu5]-DAG(1–5) was log DO/W=-2.68±0.05, pH 7.4. Receptor affinity of the nonradioactive conjugate [Lu-DTPA-(PABn)-Leu5]-DAG(1–5) was IC50 (21.06 nmol/l), as shown against the [131I]-DAG(1–28) used as a competitor. The 3-(4, 5-dimethyldiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay indicated the significant cytotoxicity of the newly synthesized compounds, similar to that of [131I]-Tyr4-DAG(1–5). Conclusion: The results obtained suggest the potency of the [DTPA-(PABn)-Leu5]-DAG(1–5) as a new carrier of radionuclides in radiopharmacy. Abstract : Supplemental Digital Content is available in the text.